Interaction in Online Learning Environments - Akçay, Arif; Çoklar, Ahmet Naci (IGI Global, 2021)
Interaction is simply defined as the interacting components communicating with each other. It is a necessary activity to ensure learning in learning environments. Unlike other learning environments, online learning environments have many requirements. Being in an environment where the learning process is not controlled causes the student to impose learning responsibilities on himself. On the other hand, in online learning environments, it is expected that the student increase academic success, ensure satisfaction, create motivation, meet social needs, acquire different perspectives, and cooperate. When the assumptions of the theories put forward to provide these positive gains in the literature are examined, it is seen that interaction has an important place. In this study, online learning environments that can provide different types of interaction are discussed. The benefits and limitations of these environments are indicated. Furthermore, suggestions have been made to support interaction in learning.
Keywords: 9. Industry and infrastructure; 4. Education; 10. No inequality; 3. Good health